AMELIORATION OF MERCURIC CHLORIDE TOXICITY ON RAT LIVER WITH ARGAN OIL AND SODIUM SELENITE SUPPLEMENTS. - YOUCEF NECIB; AHLEM BAHI; SAKINA ZERIZER (International Journal of Pharma and Bio Sciences, 2013)
The aim of the present study was investigate the impact of the combined administration of sodium selenite and argan oil on mercuric chloride toxicity. Rats were exposed to mercuric chloride (0.25 mg/kg b.w intraperitoneal injection), or argan oil (5ml/kg b.w by gavage), or sodium selenite (0.25 mg/kg b.w by gavage), or a combination of both for 3weeks. Lipid peroxidation (LPO), reduced glutathione (GSH) levels and glutathione peroxidase (GSH-Px), glutathione –S-transferase (GST) and catalase activities were carried out in liver. Serum protein, albumin levels and transaminases (AST, ALT), ALP activities were determined, histological changes in the liver was investigated. Argan oil and sodium selenite supplementation restored the increase in lipid peroxidation level and AST, ALT, ALP activities caused by HgCl2. The levels of protein, albumin, GSH and activities of antioxidant enzymes reduced by HgCl2 exposure were restored by combined administration of argan oil and sodium selenite in rats. Also, the morphological damage in the liver was reduced and the tissues appeared like those of controls. The present study suggests that combined supplementation with argan oil and sodium selenite highly protected rats from mercuric chloride toxicity.